STUDENTS ENGAGEMENT PROFILES IN ENGLISH FOREIGN LANGUAGE CLASS - Mimin Aminah (LPSDI Bina Patria, 2024)
Engagement is an important aspect to increase learning outcomes. No matter how great the teaching methods or media are, they will not be optimal without students involvement in the learning process. Data shows that the level of student engagement influences students' grade point average, hereafter GPA. Data was obtained from university students in their second year of undergraduate education who tried to explore the relationship between the GPA obtained by students by comparing it with observation data on their level of engagement with the learning they received. Data shows that students with GPAs at high, moderate and low levels are directly proportional to the level of student engagement in learning. Based on research findings, the factor that could be behind the increase in GPA is that students' learning engagement influences students' level of awareness, curiosity and persistence in learning. So that students with good learning engagement will be aroused by curiosity about a topic, try to find additional information and solutions to solve problems, and be able to persist with the challenges they are trying to solve